Attitude toward elderly patients among nursing students and clinical facilitators in Universiti Sains Malaysia (USM) - Zamri, Nurul Ezatti (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The elderly defined as those aged 60 or above that equivalent to retirement ages (World Health Organization, 2016). As the increasing of the elderly population, more nurses with the right attitude, adequate knowledge and skill also must be on the increase. A cross-sectional study was carried out to study the attitude toward elderly patients among nursing students and clinical facilitators in Universiti Sains Malaysia (USM). The questionnaire used in this study was self-administered and for attitude, the questionnaires was adapted from Hilt & Lipschultz (1997). A total of 211 respondents in USM who fulfilled the inclusion and exclusion criteria were selected randomly. Data collected were statistically analyzed using the SPSS software version 25.0. Fisher’s exact test was used for data analysis. As for the level of attitude, the results show 94 (93.1%) for positive attitude among nursing student and 19 (95.0%) among clinical facilitators, respectively. Next, there is no association between attitude toward elderly patients among nursing student and clinical facilitators (p = 1.000), respectively. Generally findings of this study show there was no association between clinical experience and attitude among nursing students (p = 1.000). In conclusion, most respondents have a high level of a positive attitude toward elderly patients. However, they still need to increase and improve their attitude, especially among nursing students. They will be nurse’s liner who are more knowledgeable and skilful in delivering care to the elderly in the future.